Fatal Retroperitoneal Bleeding in Neurofibromatosis Type 1: A Clinically Occult Complication. (18th March 2023) - Voudouri, Mariana; Chambers, Meagan; Baker, Michael L.; Kerr, Darcy A.
Abstract: Neurofibromatosis type 1 (NF1) is a common, autosomal dominant neurocutaneous syndrome. The most frequent clinical manifestations include multiple neurofibromas, café-au-lait spots, dystrophic scoliosis, benign and malignant peripheral nerve sheath tumors, and paragangliomas. Neurofibromatosis type 1 vasculopathy is a less well-recognized constellation of vascular pathologies that can cause significant medical complications in patients with NF1. A rare manifestation of this process is neurofibroma infiltration of vasculature with resultant bleeding. The case presented herein illustrates a rare example of a massive fatal hemorrhage due to disruption of a large paraspinal artery in the setting of a diffuse, infiltrative neurofibroma. This case highlights the potential of benign neurofibromas to infiltrate major blood vessels, leading to extensive bleeding and death.